1996
DOI: 10.1364/ol.21.002005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman amplification of femtosecond pulses in hydrogen gas

Abstract: We report efficient amplification of weak femtosecond supercontinuum pulses by a stimulated Raman scattering process in pressurized H(2) gas excited with 350-fs-duration frequency-doubled pulses from a regenerativeamplified Ti:sapphire laser. An amplification factor of 10(9) is obtained at the wavelength of 465 nm for seed pulses produced by supercontinuum generation in glass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The pressure also affects the wavelength range in which the amplification is observed. Amplification of light has also been reported in previous research using another third-order nonlinearity, stimulated Raman scattering [26][27][28][29]. The amplification relies on the nonlinearity originating from the nuclear response of molecules.…”
Section: Excitation Of Rotational Wavepackets By the Pump Pulse And Tsupporting
confidence: 54%
“…The pressure also affects the wavelength range in which the amplification is observed. Amplification of light has also been reported in previous research using another third-order nonlinearity, stimulated Raman scattering [26][27][28][29]. The amplification relies on the nonlinearity originating from the nuclear response of molecules.…”
Section: Excitation Of Rotational Wavepackets By the Pump Pulse And Tsupporting
confidence: 54%
“…However, an increase in pump energy leads to the appearance of self-focusing and the continuum generation, while the stretching of pulse duration to 2.4 ps effectively reduced these competing non-linear effects. Krylov et al 22 used the second harmonic of a Ti : sapphire laser with a pulse duration of 200 fs to excite SRS in compressed H 2 gas and observed threefold broadening (from 70 to 210 cm 1 ) of a depleted pump pulse and the spectral bandwidth of 150 cm 1 for the first Stokes component. The observed features have been associated with the self-phase modulation.…”
Section: Introductionmentioning
confidence: 98%
“…Bespalov et al 23 excited SRS in compressed H 2 gas using the second harmonic of a Ti : sapphire laser with a pulse duration of 400 fs and a spectral bandwidth of 70 cm 1 and found the broadening of a pump spectrum similar to that described above. 22 The spectral bandwidth of the first Stokes component was found to depend on the degree of focusing of the laser beam and became as wide as 200 cm 1 . In addition, the generation of an extended spectral continuum was observed.…”
Section: Introductionmentioning
confidence: 99%
“…[8,18], the beam profile and the divergence of the SRS radiation were badly dependent on the intensity of the pump beam, which may represent a limitation in beam shaping of the Raman laser output. There are reports on Stimulated Raman amplification with picosecond excitation, and it was found that it was useful to apply seeding to reduce the pumping threshold and improve the parameter of the Stokes-shifted radiation in the transient regime [16,[19][20][21]. Recently, Vodchits and co-workers have conducted experimental investigation on OPA used as an energy amplifier for amplifying multi-frequency SRS pulses generated in a gas mixture of compressed hydrogen and methane.…”
Section: Introductionmentioning
confidence: 99%